A Novel Synthetic Oleanolic Acid Derivative Inhibits Glioma Cell Proliferation by Regulating Cell Cycle G2/M Arrest - Tai-Hsin Tsai; Cheng-Yu Tsai; Sin-Hua Moi; Chieh-Hsin Wu; Kuan-Ting Lee; Yi-Chiang Hsu; Yu-Feng Su (MDPI AG, 2023)
2-Cyano-3,12-dioxooleana-1,9(11)-dien-28-oic acid-9,11-dihydro-trifluoroethyl amide (CDDO-dhTFEA) has antioxidant and anti-inflammatory activities; however, whether CDDO-dhTFEA has anticancer effects is unclear. The objective of this research was to investigate the possibility of CDDO-dhTFEA as a potential cancer-fighting treatment in glioblastoma cells. Our experiments were performed on U87MG and GBM8401 cells, and we found that CDDO-dhTFEA was effective in reducing cell proliferation in both cell lines, in a manner that was dependent on both time and concentration. Additionally, we observed that CDDO-dhTFEA had a significant impact on the regulation of cell proliferation, which was evident in the increase in DNA synthesis that was observed in both cell types. CDDO-dhTFEA induced G2/M cell cycle arrest and mitotic delay, which may be associated with the inhibition of proliferation. Treatment with CDDO-dhTFEA led to cell cycle G2/M arrest and inhibited proliferation of U87MG and GBM8401 cells by regulating G2/M cell cycle proteins and gene expression in GBM cells in vitro.